Ветхозаветные мотивы в образе Теодориха Великого в Excerpta Valesiani - Bespalchikova I. E. (Студенческая наука XXI века, 2015)
The author explores representation and notions of political power in the Early Middle Ages. This article shows that some features of Theodoric the Great's figure from Anonymus Valesianus could be compared with features of king Solomon image from the third book of the Kings.
Keywords: Италия; образы власти; репрезентация власти; Теодорих Великий; Excerpta Valesiani; Chronica Theodericiana; Соломон; Ветхий Завет; Раннее Средневековье; остготы; representation of political power; images of power; Theodoric the Great; Solomon; Old Testament; the Early Middle Ages; Italy; Ostrogoths